“Not in the Atlantic Provinces”:: “Not in the Atlantic Provinces”: The Abortion Debate in New Brunswick, 1980-1987 - Ackerman, Katrina (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2012)
Correspondence between Premier Richard Hatfield’s Progressive Conservative government and pro-choice and pro-life activists indicates that regionalism and religion were central to the pervasiveness of pro-life ideology and the rejection of pro-choice arguments between 1980 and 1987. Despite statistical evidence that proved abortion services were inaccessible, the government received assistance from the medical community to pass anti-abortion legislation that prohibited abortion clinics and appeared to maintain the status quo. This article provides a regional perspective on the history of abortion in Canada, but it more importantly probes how religious and cultural beliefs shaped politics and society.